Fenologia, produção e qualidade da água de coqueiro anão sob adubação potássica no Oeste Potiguar - Câmara, Francisco Mickael de Medeiros (Universidade Federal Rural do Semi-Árido, 2016)
Phenology may be defined as the study of periodicals events of plant s life, depending on their reaction to environmental conditions, and its importance is related to the management that can be developed for crops in response to these results. Aiming to evaluate the phenology of the coconut tree, an experiment was carried in the didactic orchard of the Universidade Federal Rural do Semi-Árido-UFERSA. The experimental area consisted of four-year old coconut trees of green dwarf variety, propagated by seeds and planted at a spacing of 7.5 m x 7.5 m, irrigated by microsprinkler. We selected randomly forty plants for which we made every week phenological observations during the period of January to October 2015. We analyzed as following variables: plant height, length and diameter of stem, leaf n°14 length, emission of 2nd, 3rd and 4th raceme, number of living leaves, total plants inflorescence, average number of fruits with 5, 6, 7 and 8 months of age, total number of fruits and percentage of abortion in the raceme with 5, 6, 7 and 8 months old. The vegetative and reproductive traits are influenced by the age of the plant as well as the climatic conditions
Phenology, production and coconut water quality dwarf under potassium fertilization in West Potiguar
Keywords: Coqueiro anão; Adubação potássica; Fruticultura - Oeste Potiguar; Água de coqueiro anão - Qualidade; Dwarf coconut tree; Fertilizing potassium; Fruticultura - West Potiguar; dwarf coconut water - Quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA